LEGAL IMPLICATIONS OF UNREGISTERED MARRIAGES ON THE ADMINISTRATIVE POPULATION STATUS OF CHILDREN FROM THE PERSPECTIVE OF LAW NO. 24 OF 2013: (Case Study: No. 865/Pdt.P/2024/PA/CBN) - Natasya, Jessika Angely (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
Siri marriage is a form of marriage conducted in accordance with religious law, but not officially registered with the relevant state agency, in this case the Office of Religious Affairs (KUA). This phenomenon is still widely found in Indonesia and raises complex legal issues, one of which relates to the administrative status of children born from such marriages. This issue is crucial because the registration of marriage has direct implications for the civil rights of children, including the possession of a birth certificate as a basic document in the population administration system. This study aims to analyze the legal implications of unregistered marriages on the administrative status of children in the context of Law No. 24 of 2013 on Population Administration, by examining the Cibinong Religious Court Decision No. 865/Pdt.P/2024/PA/CBN as a case study. The method used is a normative juridical approach with data collection through a literature review of legal literature, court decisions, laws and regulations, and relevant academic articles.                 The results of the study show that children born from unregistered marriages often face obstacles in obtaining birth certificates because their parents do not meet the requirements for marriage registration. This situation results in uncertainty regarding the legal status of the child in the eyes of the state, particularly in relation to civil rights and legal protection. However, through the mechanism of marriage validation, the court provides validation of unregistered marriages so that children can obtain administrative legality. The decision of the Cibinong Religious Court in the case studied confirms that the state is present to provide legal certainty for children, while reinforcing the importance of marriage registration as an instrument for the protection of civil rights. This study confirms that marriage registration is a fundamental aspect of guaranteeing children's rights in population administration.